The dependence of composition, microstructure and properties of electroplated Ni – Sn coatings on conditions of deposition from fluoride-chloride electrolyte - Vorobyova, Tatsiana N.; Kudaka, Anton A. (Journal of the Belarusian State University. Chemistry, 2017)
Composition and working conditions of stable fluoride-chloride electrolyte with the diminished nickel chloride content have been found based on the experimental data on the effect of pH, current density, the nature and concentration of components on composition, microstructure and properties of the electrodeposited nickel – tin alloy. In the absence of modifying additives this electrolyte provides plating of uniform, dense and unstressed Ni – Sn coatings which consist of dominating Ni3Sn4 phase and contain 35 at. % of nickel. These coatings have the raised corrosion stability and solderability for a long period of aging. The principal effect of the electrolyteʼs pH (optimal 4.0) on the stability of the solution and coatings quality has been shown. It is revealed that nickel and tin simultaneous reduction proceeds with the depolarizationN effect stipulated by the alloy formation.
Keywords: electrolyte composition; pH; alloy; elemental and phase composition; intermetallic; properties of coatings; depolarization